Publication Output of Bahir Dar University: A Scopus-based Bibliometric Overview - Yallew, Addisalem Tebikew; Dereb, Asrat (Bahir Dar Journal of Education, 2023)
Bahir Dar University (BDU) is one of Ethiopia's oldest and leading universities and has recently been granted the status of a research university within the country's system of differentiation of higher education. Despite this, there has been a lack of systematic mapping of the research output of the university. To address this issue, this study takes a 22-year dataset of publications from Scopus to analyze publication output affiliated with the university as represented in the international domain. The analysis encompasses several dimensions, including overall productivity, collaboration patterns, dominant research areas, primary publication outlets, and languages of publication. The findings reveal a notable increase in research productivity at the university since 2010. The top five research areas impacting this productivity include medicine, agriculture, environmental science, social sciences, and engineering. In addition, the majority of publications are found to be published in biomedical science journals, English being the dominant language of publication. Though at the institutional level, the university’s collaborators are predominantly other Ethiopian public universities, at the country level, BDU’s top collaborators come from the USA, Germany, South Africa, the UK, Japan, and Belgium. Based on the results, we argue that the university still needs a robust research funding and incentivization system, though research productivity has considerably improved over the past two decades. Furthermore, we recommend that the university's journals, which the Ministry of Education has accredited, be indexed in reputable international journal databases to enhance their visibility.